Analisis Bencana Tanah Longsor di Wilayah Provinsi Jawa Tengah - rizkyah isnaini (Islamic Management and Empowerment Journal, 2019)
Landslides are one of the disasters that often occur in Indonesia. Central Java Province is an area that has the potential to experience landslides due to varied morphological forms such as plateaus and hills. This study aims to analyze the causes, impacts and management of disaster management. This research uses a qualitative method with a descriptive approach. The data is obtained from supporting data such as BNPB, Central Java BPBD, related scientific articles, and media. The results showed that the impact of landslides threatens the sustainability of the community's life and the causes are high rainfall conditions, steep slope topography, erosion-prone soil conditions, land use is important to be considered to prevent and overcome future landslides.